2004
DOI: 10.1111/j.1460-9568.2004.03193.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunogold investigation of the distribution of GABA and glycine in nerve terminals on the somata of spherical bushy cells in the anteroventral cochlear nucleus of guinea pig

Abstract: Spherical bushy neurons in the anteroventral cochlear nucleus receive glutamatergic primary terminals from the cochlear nerve and terminals of noncochlear (i.e. nonprimary) origin, many of which colocalize gamma-aminobutyric acid (GABA) and glycine. Here the relationship between GABA and glycine in these terminals has been investigated using postembedding immunogold labelling. A significant negative correlation was found between the density of terminal labelling for GABA and for glycine in four guinea pigs. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
(150 reference statements)
3
16
0
Order By: Relevance
“…Since the analysis of our data confirmed earlier results by Caspary et al (1993Caspary et al ( , 1994, and Backoff et al (1997), who also found no differences between bicuculline and strychnine application in AVCN bushy cells, we subjected experiments with both drugs to an integrated analysis. This is in accordance with the immunocytochemical verification of GABA and glycine colocalization in afferent structures of the SBCs (Juiz et al, 1996;Mahendrasingam et al, 2004). To exclude the possibility that the observed effects were due to others than effects of the respective drugs, we performed control experiments (n ¼ 9), where the carrier was applied without the drug.…”
Section: Resultssupporting
confidence: 55%
“…Since the analysis of our data confirmed earlier results by Caspary et al (1993Caspary et al ( , 1994, and Backoff et al (1997), who also found no differences between bicuculline and strychnine application in AVCN bushy cells, we subjected experiments with both drugs to an integrated analysis. This is in accordance with the immunocytochemical verification of GABA and glycine colocalization in afferent structures of the SBCs (Juiz et al, 1996;Mahendrasingam et al, 2004). To exclude the possibility that the observed effects were due to others than effects of the respective drugs, we performed control experiments (n ¼ 9), where the carrier was applied without the drug.…”
Section: Resultssupporting
confidence: 55%
“…Anatomical studies in mature guinea pigs and rats have shown glycinergic, GABAergic and terminals colocalizing GABA and glycine on SBCs (Juiz et al, 1996; Mahendrasingam et al, 2000, 2004; Luján et al, 2008). Consistent with these results, the present data show putative glycinergic and GABAergic inputs on SBCs and, in addition, ~1/5 of pixels colocalizing markers for both transmitters at P25 and P60 (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…These SBCs receive suprathreshold excitatory input from auditory nerve fibers (ANF) via large axosomatic terminals, the endbulbs of Held (Brawer and Morest, 1975; Schwartz and Gulley, 1978; Ryugo and Sento, 1991; Nicol and Walmsley, 2002). In addition, inhibitory inputs on SBCs have been reported, which provide surprisingly slow acoustically evoked inhibition mediated by glycine and GABA (Wu and Oertel, 1986; Kolston et al, 1992; Juiz et al, 1996; Lim et al, 2000; Mahendrasingam et al, 2004; Xie and Manis, 2013), with glycine dominating (Nerlich et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%